2021
DOI: 10.3390/jcm10010157
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Trajectories across 10 Years after Moderate to Severe Traumatic Brain Injury in Norway

Abstract: Traumatic brain injury (TBI) has a long-lasting impact on participation and health-related quality of life (HRQL). We aimed to describe the physical and mental health trajectories and to identify their predictors across the first 10 years after TBI. A prospective longitudinal cohort of 97 individuals with moderate to severe TBI (age 16–55 years) in Norway were followed up at 1, 2, 5, and 10 years post-injury. Their socio-demographic and injury characteristics were recorded at baseline; their responses to the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Persons who suffer a TBI might experience a variety of consequences, including difficulties with physical, cognitive, emotional, behavioral, vocational, and social functioning. Many experience persistently reduced quality of life and restrictions in community participation [4][5][6][7][8][9]. Families are also affected and may have to adapt to a new life with their injured family member being dependent on their assistance and support [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Persons who suffer a TBI might experience a variety of consequences, including difficulties with physical, cognitive, emotional, behavioral, vocational, and social functioning. Many experience persistently reduced quality of life and restrictions in community participation [4][5][6][7][8][9]. Families are also affected and may have to adapt to a new life with their injured family member being dependent on their assistance and support [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The physical, cognitive and emotional consequences of traumatic brain injury (TBI) may have a substantial negative impact on daily life functioning and quality of life [1,2]. The goal of TBI rehabilitation is to maximize the final outcome and preferably restore the preinjury functional level.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the age factor, our study is in line with a recent multi-centre study which found that women reported more severe outcomes, depending on TBI severity and older age [ 24 ]. A recent prediction study reported that women, persons who were unemployed before injury and persons with more severe TBI at 10-year follow-up had lower HRQL, suggesting that these persons should perhaps be targeted for regular follow-up [ 62 ]. However, there were only seven female participants in our study, and, therefore, it is not possible to draw any major conclusions regarding whether being a woman has any significance for the outcome.…”
Section: Discussionmentioning
confidence: 99%